Penambahan Sayuran Bayam pada Pengolahan Stik Berbasis Tepung Mocaf dan Tepung Terigu - Budi Santoso; Herfriyanti Ronasari; Parwiyanti Parwiyanti; Hermanto Hermanto (Seminar Nasional Lahan Suboptimal, 2020)
Santoso B, Ronasari H, Parwiyanti P, Hermanto H.  2020. Addition of Spinach in Proccesing Stick Base on Cassava Flour Modification and Wheat Flour, In: Herlinda S et al. (Eds.),  Prosiding Seminar Nasional Lahan Suboptimal ke-8 Tahun 2020, Palembang 20 Oktober 2020. pp. xx. Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).Research objective was to study physical and chemical characteristics stick base on pureed spinach and combination of cassava flour modification and wheat flour. Experimental research used non factorial block randomized design with two treatments.  The treatment were pureed spinach and combination of cassava flour modification and wheat flour ratio A=0:100%; B=10:90%; C=20:80%; D=30:70%, and E=40:60%, respectively.  Observed parameters were color (lightness, coma, and hue), texture, water content, carotene total, and fiber content.  The result showed that pureed spinach and combination of cassava flour modification and wheat flour ration had significantly effected on color, texture, water content, carotene total, and fiber content.  Physical and chemical characteristic of stick were lightness 35,15-55,30%, croma 12,28-23,23%, hue 96,83-176,85%, texture 796,23-1278%, water content 1,64-7,57%, fiber content 0,39-1,48%, and carotene total 13,51-56,36%.